Midgut microbiota affects the intestinal barrier by producing short-chain fatty acids in Apostichopus japonicus - Song, Mingshan; Zhang, Zhen; Li, Yanan; Xiang, Yangxi; Li, Chenghua (Frontiers in Microbiology, 2023)
Introduction The intestinal microbiota participates in host physiology and pathology through metabolites, in which short-chain fatty acids (SCFAs) are considered principal products and have extensive influence on intestine homeostasis. It has been reported that skin ulceration syndrome (SUS), the disease of Apostichopus japonicus caused by Vibrio splendidus, is associated with the alteration of the intestinal microbiota composition. Method To investigate whether the intestinal microbiota affects A. japonicus health via SCFAs, in this study, we focus on the SCFA profiling and intestinal barrier function in A. japonicus treated with V. splendidus. Results and discussion We found that V. splendidus could destroy the mid-intestine integrity and downregulate the expression of tight junction proteins ZO-1 and occludin in A. japonicus, which further dramatically decreased microorganism abundance and altered SCFAs contents. Specifically, acetic acid is associated with the largest number of microorganisms and has a significant correlation with occludin and ZO-1 among the seven SCFAs. Furthermore, our findings showed that acetic acid could maintain the intestinal barrier function by increasing the expression of tight junction proteins and rearranging the tight junction structure by regulating F-actin in mid-intestine epithelial cells. Thus, our results provide insights into the effects of the gut microbiome and SCFAs on intestine barrier homeostasis and provide essential knowledge for intervening in SUS by targeting metabolites or the gut microbiota.